IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KOLABORASI SISWA - Fatikhatus Sarifah; Tutut Nurita (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This study aimed to describe the improvement of students’ critical thinking and collaboration skills using a guided inquiry learning model implemented in one of the public Junior High Schools in Gresik. This study was a pre-experimental with one group pretest-posttest design. The subjects in this study involved 32 students in VII grade. Data collection techniques through a test and observation by applied in the form of written tests and student collaboration skills observation sheets as the instruments. The findings revealed that there was an improvement in the student’s critical thinking skills as evidenced by the average value of the N-Gain score in the high category. The result of the Wilcoxon test showed that student critical thinking skills were significantly better. Students’ collaboration skills were increased at each meeting, from a less collaborative to a very collaborative category. Based on the results obtained, it can be concluded that the guided inquiry learning models implementation improved students’ critical thinking and collaboration skills.